2001
DOI: 10.1093/phr/116.s1.103
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of a Peer-Based Intervention to Promote Condom and Contraceptive Use among HIV-Positive and at-Risk Women

Abstract: Objective. The authors used data from a larger study to evaluate the longterm effects of a peer advocate intervention on condom and contraceptive use among HIV-infected women and women at high risk for HIV infection.Methods. HlV-infected women in one study and women at high risk for HIV infection in a second study were selected from the Women and lnfants Demonstration Project and assigned to a standard or an enhanced HIV prevention treatment group. The enhanced intervention included support groups and one-on-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…In closing, an impressive number of studies have demonstrated the efficacy of interventions to persuade and train people to use condoms (see Cottler et al 1998;Fogarty et al 2001;Healton and Messeri 1993;Kalichman et al 1996;Kegeles et al 1996;Kelly et al 1991Kelly et al , 1992Kelly et al , 1997Lauby et al 2000;MacLachlan et al 1997;McCusker et al 1996; National Institute of Mental Health [NIMH] Multisite HIV Prevention Trial Group, 1998;O'Leary et al 1998;Rotheram-Borus et al 2001;CDC AIDS Community Demonstration Projects Research Group, 1999). However, these studies have never considered the actual reach of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In closing, an impressive number of studies have demonstrated the efficacy of interventions to persuade and train people to use condoms (see Cottler et al 1998;Fogarty et al 2001;Healton and Messeri 1993;Kalichman et al 1996;Kegeles et al 1996;Kelly et al 1991Kelly et al , 1992Kelly et al , 1997Lauby et al 2000;MacLachlan et al 1997;McCusker et al 1996; National Institute of Mental Health [NIMH] Multisite HIV Prevention Trial Group, 1998;O'Leary et al 1998;Rotheram-Borus et al 2001;CDC AIDS Community Demonstration Projects Research Group, 1999). However, these studies have never considered the actual reach of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that HIV secondary prevention interventions are more successful when interventionists are medical providers or counselors [18]; however, the few studies that have utilized HIV-infected peer-interventionists to counsel HIV-infected individuals have promising findings [19,20]. There are several advantages to a peerbased approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although a handful of proven behavioral interventions exist to help both men and women with HIV/ AIDS decrease their risky sexual practices (Fisher et al 2006;Gilbert et al 2008;The Healthy Living Project Team 2007;Kalichman et al 2001;Patterson et al 2003;Richardson et al 2004;Sikkema et al 2007), we are aware of few published interventions that are tailored to the specific needs of WLH/A (Fogarty et al 2001;Wingood et al 2004). Because women and men face vastly different safer sex challenges, such tailored interventions are necessary.…”
Section: Introductionmentioning
confidence: 99%